2015
DOI: 10.1021/acsami.5b08302
|View full text |Cite
|
Sign up to set email alerts
|

Stretch-Induced Helical Conformations in Poly(l-lysine)/Hyaluronic Acid Multilayers

Abstract: We investigate the effect of stretching on the secondary structure of cross-linked poly(l-lysine)/hyaluronic acid (PLL/HA) multilayers. We show that stretching these films induces changes in the secondary structure of PLL chains. Our results suggest that not only α- but also 310-helices might form in the film under stretching. Such 310-helices have never been observed for PLL so far. These changes of the secondary structure of PLL are reversible, i.e., when returning to the nonstretched state one recovers the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The spectra with two minima are typical of α-helix conformations. They cannot be attributed to HA chains, as it is known that in solution at pH 7.4 HA has an unordered conformation . This indicates that PAR chains should change from a coil conformation in solution to an α-helix in the film.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The spectra with two minima are typical of α-helix conformations. They cannot be attributed to HA chains, as it is known that in solution at pH 7.4 HA has an unordered conformation . This indicates that PAR chains should change from a coil conformation in solution to an α-helix in the film.…”
Section: Resultsmentioning
confidence: 97%
“…They cannot be attributed to HA chains, as it is known that in solution at pH 7.4 HA has an unordered conformation. 30 This indicates that PAR chains should change from a coil conformation in solution to an α-helix in the film. A similar behavior was previously observed for LbL built up with poly(lysine) and poly(glutamic acid).…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
“…Indeed, the pKa of HA in solution is reported to be 3.0 and that of PL about 10 [29]. Moreover, it is reported that PL presents secondary structures that vary with pH in aqueous solution, adopting a random coil conformation under acidic and neutral conditions, and undergoing a coil-to helix transition under basic conditions [41]. Thus, we assumed that PL conformation at pH 6 is essential for maximizing PL interactions with HA.…”
Section: Nanogels Formulative Studiesmentioning
confidence: 97%
“…The design of novel functional biomaterials is nowadays focused on the employment of biobased polymers capable of responding to external stimulus, such as magnetic fields, temperature, pH, , light, , electrochemical potentials, and mechanical signals , in a well-controlled manner . Stimuli-responsive hydrogels are widely employed in different applications such as drug delivery, tissue engineering, sensors, actuators, and energy storage .…”
Section: Introductionmentioning
confidence: 99%